Analisis Penjualan, Beban Umum dan Administrasi terhadap Laba Bersih pada Kalbe Farma Tbk Periode 2006 - 2017 - Santi Widiawati (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2020)
This research aims to examine the influence of sales to net income in PT Kalbe Farma Tbk for the period 2006-2017, the influence of general & administrative expenses to net income in PT Kalbe Farma Tbk for the period 2006- 2017, and the influence of sales, general & administrative expenses simultaneously to net income in PT Kalbe Farma Tbk period 2006-2017. The data used in this research is secondary data sourced from the financial statements of PT Kalbe Farma Tbk for the period 2006-2017 by accessing www.kalbe.co.id. The object of this research is PT Kalbe Farma Tbk. This type of research is comparative causal research. This study uses the method of multiple linear regression analysis using the classical assumption test and hypothesis testing. Data was collected by library research and documentation and analyzed using the SPSS version 23 application. Based on the results of the research using the t test concluded that sales have a significant influence to net income, where the value of t count> t table (2.338> 2.262) and general & administrative expenses do not have a significant influence to net income, where the value of t count <t table (0.113 <2,262 ). Based on the f test it can be concluded that sales, general & administrative expense simultaneously have a significant influence to net income, where f count> f table (14,285> 4.46).